2016
DOI: 10.1111/gcb.13279
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for divergence of response in Indica, Japonica, and wild rice to high CO2 × temperature interaction

Abstract: High CO2 and high temperature have an antagonistic interaction effect on rice yield potential and present a unique challenge to adapting rice to projected future climates. Understanding how the differences in response to these two abiotic variables are partitioned across rice germplasm accessions may be key to identifying potentially useful sources of resilient alleles for adapting rice to climate change. In this study, we evaluated eleven globally diverse rice accessions under controlled conditions at two car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 32 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…As indicated earlier, future climatic scenarios with e[CO 2 ] accompanied by higher temperature presents a unique challenge for crop improvement due to antagonistic interaction of these factors 31 , 32 . Despite higher growth and yield, e[CO 2 ] grown plants could be more sensitive to higher temperatures due to reduced stomatal conductance and transpiration under e[CO 2 ] 31 , 61 (Fig. 1 ; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated earlier, future climatic scenarios with e[CO 2 ] accompanied by higher temperature presents a unique challenge for crop improvement due to antagonistic interaction of these factors 31 , 32 . Despite higher growth and yield, e[CO 2 ] grown plants could be more sensitive to higher temperatures due to reduced stomatal conductance and transpiration under e[CO 2 ] 31 , 61 (Fig. 1 ; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example heat stress resulted in reduced grain weight or grain starch content even with higher sucrose supply from source tissue under e[CO 2 ] in rice 29 , 30 . Recent studies reveal that rice plants grown under e[CO 2 ] were more sensitive to heat stress compared to plants grown under ambient conditions 31 . Alternatively e[CO 2 ] failed to compensate for the negative impact of heat stress on yield 32 suggesting temperature to be the major driver inducing damage under e[CO 2 ] + HT interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term expectations should be tempered until effects of other climatic parameters (e.g. rising atmospheric CO 2 ) on pre-heading stem NSC are better understood, as they may have unexpected interaction effects (Moya et al , 1998; Baker, 2004; Ziska et al , 2014; Wang et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have confirmed that there is significant intraspecific variation in the yield response to future CO 2 levels for cowpea (Vigna unguiculata (L.) Walp.) 7 ; common bean (Phaseolus vulgaris L.) 8 , rice (Oryza sativa L.) [9][10][11] ; wheat (Triticum aestivum L.) 12,13 and soybean (Glycine max (L.) Merr.) 14 , such that breeders could begin to select for CO 2 responsiveness among currently available germplasm.…”
mentioning
confidence: 99%